Penerapan Metode User Centered Design pada Rancangan User Interface Marketplace Pemasaran Produk Olahan Perikanan - Fauzan Natsir; Redo Abeputra Sihombing (Journal of Practical Computer Science, 2022)
Activities that support various activities in the fisheries sector, one of which is processed fish products, seeks to improve the economy of the community, especially fishermen in processing marine products. One of the efforts is to expand the distribution of processed seafood and penetrate the market through designing a user interface for the processed seafood distribution system. The method applied in this study is User Centered Design (UCD) with a design philosophy that places the user at the center of the system development process. The UCD approach is supported by techniques, tools, procedures, and processes that help design interactive systems that are more user centric. Based on usability testing that uses a usability scale system, the marketplace user interface model for marketing processed fish products is assessed with a yield of 86.5%. So that this marketplace user interface design mockup has been rated as user friendly which is indicated using high functionality and in accordance with the design. Keyword: User Centered Design (UCD), user interface, marketplace, processed fish.